2023
DOI: 10.3390/jcm12020552
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Plasma Syndecan-1 Predicts 60-Day Mortality in Patients with COVID-19

Abstract: Background: Endotheliopathy is a common pathologic finding in patients with acute and long COVID-19. It may be associated with disease severity and predispose patients to long-term complications. Plasma levels of a proteoglycan, syndecan-1, are found to be significantly elevated in patients with COVID-19, but its roles in assessing disease severity and predicting long-term outcome are not fully understood. Methods: A total of 124 consecutive hospitalized patients with SARS-CoV-2 infection were prospectively en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Endotheliopathy, marked by the increased levels of plasma VWF (32,33) and syndecan-1 (4) , has been previously shown to be associated with the disease severity. It may predispose to a long-term cardiovascular complication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endotheliopathy, marked by the increased levels of plasma VWF (32,33) and syndecan-1 (4) , has been previously shown to be associated with the disease severity. It may predispose to a long-term cardiovascular complication.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were divided into 4 groups: asymptomatic, moderate, severe, and critical groups based on an updated WHO guideline. The demographic, clinical, and laboratory characteristics of this cohort of patient were previously described (4) .…”
Section: Demographic Clinical and Laboratory Characteristics Of The C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The level of glycocalyx damage may be dependent on COVID-19 severity, as in vitro findings indicate that blood derived from patients with mild symptoms reduced the glycocalyx by approximately 49%, whereas sera from patients with severe symptoms reduced the height of the glycocalyx by >60% [40]. COVID-19 severity is also related to the magnitude of elevation in blood concentrations of syndecan-1, heparinase, heparin sulfate, and hyaluronan [37,40,41 ▪▪ ,42,43,44 ▪ ,45]. The loss of syndecan-1 from the endothelial glycocalyx leads to increased adhesion of leukocytes to endothelial cells, enhanced vascular permeability, and intravascular coagulation [39,40,46], which is a major concern as glycocalyx damage could increase the severity of inflammatory response to COVID-19, as well as the length of recovery.…”
Section: Coronavirus Disease 2019mentioning
confidence: 99%
“…Many studies have demonstrated that endothelial injury and microvascular thrombosis are associated with the pathogenic processes of severe and critical COVID-19 disease [5][6][7][8][9][10][11][12]. The vascular endothelium is a single and flat cell layer that maintains the entire balance of blood fluid hemostasis and prevents thrombosis [13,14].…”
Section: Introductionmentioning
confidence: 99%